DETERMINAN KEPUTUSAN PEMBELIAN PRODUK GREEN LABEL BERDASARKAN GREEN PRODUCT DAN GETOK TULAR - Metta Padmalia (Universitas Kristen Maranatha, 2018)
The study was conducted to identify the characteristics of consumers for products with a green label, analyzing the influence of aspects of green product and word of mouth to the label green product purchasing decisions. The sampling method using a convenience sampling, involving 100 respondents who are students in Surabaya with a minimum age of 17 years and they’ve bought green labels products. Data were analyzed using the Partial Least Squares (PLS). The results of PLS analysis shows that there is impact of green input, green output, and word of mouth to purchasing decision with coefficient value 0.2444, 0.2461, 0.4664 for each, while green process doesn’t have impact to purchase decision. These results indicate that consumers consider important aspects of green input and green output that can be felt directly, while green process can’t be felt immediately. Moreover, in deciding to buy a product green label, recommendations from others considered important by consumers.Keywords: Green Label, Green Product, Word of Mouth, Purchasing Decision